The Predicting Effect of Occupational Commitment and Leadership Styles on Organizational Effectiveness of Public School Heads - Mamasarogan, Jalaisa; Tan, Mark Raymond (Journal of Interdisciplinary Perspectives, 2024)
The research aimed to assess the predictive impact of occupational commitment and leadership styles on the organizational effectiveness of public school leaders. The results revealed that rank, years in service as school head, and type of school exhibited statistically significant differences in the school heads’ occupational commitment. On the other hand, the statistical significance test exposed that school heads’ leadership styles of transformational, transactional, and democratic leadership exhibited a significant positive association with organizational effectiveness. Furthermore, the influence test showed that occupational commitment significantly contributed to explaining the variance in organizational effectiveness among respondents. Alternatively, leadership styles, specifically transformational, transactional, and democratic, were found to be predictors of organizational effectiveness. Lastly, the multiple regression results for predicting organizational effectiveness based on the school heads’ occupational commitment and leadership styles revealed that the model fit is robust, demonstrating that the overall model is statistically significant and provides a good fit for the data. Among the independent variables under study, occupational commitment had a more important influence on organizational effectiveness. On the other hand, leadership styles also significantly predict organizational effectiveness, though with a minor impact. This indicated that while effective leadership styles positively influence organizational effectiveness, their effect is less pronounced than occupational commitment. The study underscored the importance of commitment and leadership in cultivating favorable organizational climates that facilitate collaboration, innovation, and continuous improvement.